Effect of a community health worker-led multicomponent intervention on blood pressure control in low-income patients in Argentina: A randomized clinical trial - He, Jiang (2017)
IMPORTANCE: Despite extensive knowledge of hypertension treatment, the prevalence of uncontrolled hypertension is high and increasing in low- and middle-income countries. OBJECTIVE: To test whether a community health worker–led multicomponent intervention would improve blood pressure (BP) control among low-income patients with hypertension. DESIGN, SETTING, AND PARTICIPANTS: A cluster randomized trial was conducted in 18 centers for primary health care within a national public system providing free medications and health care to uninsured patients in Argentina. A total of 1432 low-income adult patients with uncontrolled hypertension were recruited between June 2013 and April 2015 and followed up to October 2016. INTERVENTIONS: Nine centers (743 patients) were randomized to the multicomponent intervention, which included a community health worker–led home intervention (health coaching, home BP monitoring, and BP audit and feedback), a physician intervention, and a text-messaging intervention over 18 months. Nine centers (689 patients) were randomized to usual care. MAIN OUTCOMES AND MEASURES: The coprimary outcomes were the differences in systolic and diastolic BP changes from baseline to the end of follow-up of patients with hypertension. Secondary outcomes included the proportion of patients with controlled hypertension (BP <140/90 mm Hg). Three BP measurements were obtained at each of 2 baseline and 2 termination visits using a standard protocol, the means of which were used for analyses. RESULTS:      Of 1432 participants (mean age, 55.8 years [SD, 13.3]; 772 women [53.0%]), 1357 (94.8%) completed the trial. Baseline mean systolic BP was 151.7 mm Hg for the intervention group and 149.8 mm Hg for the usual care group; the mean diastolic BP was 92.2 mm Hg for the intervention group and 90.1 mm Hg for the usual care group. Systolic BP reduction from baseline to month 18 was 19.3 mm Hg (95% CI, 17.9-20.8 mm Hg) for the intervention group and 12.7 mm Hg (95% CI, 11.3-14.2 mm Hg) for the usual care group; the difference in the reduction was 6.6 mm Hg (95% CI, 4.6-8.6; P < .001). Diastolic BP decreased by 12.2 mm Hg (95% CI, 11.2-13.2 mm Hg) in the intervention group and 6.9 mm Hg (95% CI, 5.9-7.8 mm Hg) in the control group; the difference in the reduction was 5.4 mm Hg (95% CI, 4.0-6.8 mm Hg; P < .001). The proportion of patients with controlled hypertension increased from 17.0% at baseline to 72.9% at 18 months in the intervention group and from 17.6% to 52.2% in the usual care group; the difference in the increase was 20.6% (95% CI, 15.4%-25.9%; P < .001). No adverse events were reported. CONCLUSIONS AND RELEVANCE: Low-income patients in Argentina with uncontrolled hypertension who participated in a community health worker–led multicomponent intervention experienced a greater decrease in systolic and diastolic BP than did patients who received usual care over 18 months. Further research is needed to assess generalizability and cost-effectiveness of this intervention and to understand which components may have contributed most to the outcome. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT01834131.